Analysis of the determinants that motivate high school students to learn english. - Chamba Retete, Jennifer Dayanna (2024)
Motivation is a fundamental aspect of the educational context, particularly in the learning of a new language, which in this case is English. It is motivation that determines whether students persevere and succeed in overcoming the challenges associated with learning. This research examined two influential determinants in the motivation to learn English among high school students. Previous studies have indicated that this is a period when motivation-related issues tend to emerge more frequently. The student-centered approach and the recognition of the importance of English as a global language for communication and cultural exchange were established as relevant determinants. The importance of good classroom management was also emphasized. This research employed a qualitative method, and for data collection, individual interviews with secondary school English teachers from different educational institutions in the province were conducted. The findings of this research informed the identification of motivational determinants in the teaching of English, furthermore, educators will be able to implement educational strategies that enhance motivation and efficacy in the learning process.